Purification method and application of high-quality hard carbon
The purification method enhances sodium storage capacity and cycle retention rate by enhancing sodium storage capacity and sodium storage performance, and improving the sodium storage capacity and cycle retention rate.
Patent Information
- Application Number
- CN202411369149.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The challenge of finding suitable negative electrode materials for sodium-ion batteries is exacerbated by the complex composition structure of hard carbon, leading to poor sodium storage performance in inferior hard carbon tissues, limiting the overall performance of sodium-ion batteries.
A purification method involving ultrafine grinding, dispersion in a solvent solution with specific additives, and buoyancy separation to obtain high-quality hard carbon with improved sodium storage performance, utilizing ethanol, deionized water, sodium chloride, and polyvinyl pyrrolidone or polyethylene glycol to enhance dispersibility and density control.
The method results in high-quality hard carbon with enhanced sodium storage capacity and cycle stability, achieving a first discharge specific capacity of 396.2mAh/g and a retention rate of 98.0% after 100 cycles, significantly improving the sodium-ion battery's sodium storage capacity and cycle stability, and improving the sodium storage capacity and cycle retention rate.
Smart Images

Figure CN119191267A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery negative electrode materials, in particular to a purification method and application of high-quality hard carbon. Background Art
[0002] In the process of industrial development, the extensive use of fossil fuels has caused the dual dilemma of energy shortage and environmental pollution. It is urgent to accelerate the efficient utilization of green and clean energy and the development of new energy storage technologies. Among the many electrochemical energy storage technologies, sodium-ion battery energy storage technology has low cost, abundant sodium resources, and is not restricted by geographical location, and has very important application prospects. Electrode materials are an important component of sodium-ion batteries. Up to now, the development of a series of positive electrode materials has made the application of high-performance sodium-ion batteries possible. However, finding suitable negative electrode materials for sodium-ion batteries remains a challenge. Hard carbon materials are the first choice for the commercialization of sodium-ion battery negative electrodes due to their low price, abundant sources and high capacity.
[0003] However, due to the complex composition structure of the hard carbon precursor, the microstructure of the hard carbon obtained is obviously different, and some inferior hard carbon tissues have poor sodium storage performance, which limits the sodium storage performance of the final hard carbon product. How to separate and purify hard carbon to obtain high-quality hard carbon with excellent sodium storage performance is a difficult problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of low sodium storage capacity and low initial coulombic efficiency faced by hard carbon in the prior art when used as the negative electrode of sodium ion batteries. To this end, the present invention provides a purification method and application of high-quality hard carbon.
[0005] In view of the technical problems existing in the prior art, the present invention provides a method for purifying high-quality hard carbon, comprising the following steps:
[0006] (1) ultrafinely grinding hard carbon to obtain hard carbon powder;
[0007] (2) dispersing hard carbon powder in a solution and stirring to obtain a suspension;
[0008] (3) Allow the suspension to stand, separate and retain the lower layer, wash and dry to obtain the product.
[0009] Preferably, in step (1), the hard carbon is obtained by carbonizing a hard carbon raw material at high temperature under an inert atmosphere;
[0010] Preferably, the hard carbon raw material is a mixture of any one or more of starch, asphalt, bagasse, eucalyptus, glucose, straw, reed, peanut shell, palm shell or macadamia shell;
[0011] Preferably, the specific method of high temperature carbonization is: crushing the hard carbon raw material into 100 mesh, placing it in a nitrogen atmosphere furnace and calcining it at 1300° C. for 2 hours;
[0012] Preferably, in step (1), the ultrafine grinding is performed by jet mill ultrafine grinding, and the cold dry gas pressure is 0.65-1.1 MPa; the particle size D50 of the hard carbon powder is 3-50 um.
[0013] Among them, the particle size D50 of the hard carbon powder of the present invention is 3-50um. On the one hand, the hard carbon material with a particle size within this range has better sodium storage performance; on the other hand, it is convenient for subsequent purification and impurity removal of the hard carbon.
[0014] Preferably, in step (2), the solution comprises the following components, by weight: 200-400 parts of solvent, 0-80 parts of solute and 10-20 parts of additive.
[0015] More preferably, in step (2), the solvent is ethanol and / or deionized water; the solute is sodium chloride; and the additive is polyvinyl pyrrolidone or polyethylene glycol.
[0016] More preferably, in step (2), the solvent is ethanol and deionized water, and the mass ratio of ethanol to deionized water is 1:1.
[0017] Among them, the present invention uses deionized water (or ethanol) and sodium chloride to mix and control the density of the solution, thereby controlling the buoyancy of the solution. The buoyancy of hard carbon is related to its internal closed-pore structure and surface functional groups, and the closed-pore structure and surface functional groups determine the sodium storage performance of hard carbon. Among them, the present invention uses sodium chloride solution, which is green and pollution-free, easy to clean and recycle; and sodium chloride can increase the density of the solution, and then increase the buoyancy of the solution; furthermore, ethanol and deionized water, deionized water and sodium chloride can be mutually soluble in a certain proportion, and a series of solvents with different densities can be prepared by adjusting the proportion, which is convenient for the subsequent sorting of hard carbon powder.
[0018] The present invention uses polyvinyl pyrrolidone or polyethylene glycol as a dispersant to evenly disperse the hard carbon powder in the solution, prevent hard carbon from agglomerating, improve the dispersibility of hard carbon in the solution, achieve efficient separation of hard carbon, and facilitate subsequent powder separation.
[0019] More preferably, when in step (1), the hard carbon is starch, asphalt, glucose, straw, reed or peanut shell, in step (2), the solution comprises the following components by weight: 300 parts of solvent and 10 parts of additive.
[0020] More preferably, when in step (1), the hard carbon is bagasse, eucalyptus, palm shell or macadamia shell, in step (2), the solution comprises the following components, by weight: 300 parts of solvent, 30-60 parts of solute and 10 parts of additive.
[0021] Among them, during the sorting, the density of the dispersion solution used should be slightly greater than the density of the hard carbon. If the density of the dispersion solution is much greater than the density of the hard carbon, the yield of the purified sample will be reduced. At the same time, the density of the dispersion solution is not the only factor to consider. It is also necessary to ensure that the hard carbon has a rich closed-pore structure, so as to achieve a larger sodium storage capacity.
[0022] Preferably, in step (2), the mass ratio of the hard carbon powder to the solvent in the solution is 1:(50-70).
[0023] More preferably, in step (2), the mass ratio of the hard carbon powder to the solvent in the solution is 5:300 (ie 1:60).
[0024] Preferably, in step (2), the stirring speed is 400-600 rpm and the stirring time is 1-2 h.
[0025] More preferably, in step (2), the stirring speed is 500 rpm and the stirring time is 1 hour.
[0026] Preferably, in step (3), the standing time is 22-26 hours; and the drying time is 22-26 hours.
[0027] More preferably, in step (3), the standing time is 24 hours; and the drying time is 24 hours.
[0028] Preferably, in the step (3), the specific separation method is: separating the upper layer of suspended hard carbon and the lower layer of deposited hard carbon, and retaining the lower layer of deposited hard carbon.
[0029] Among them, inferior hard carbon with low density, large specific surface area, light weight and poor sodium storage performance can be removed through separation.
[0030] Preferably, in step (3), the carbon interlayer spacing of the obtained high-quality hard carbon is ≥0.38nm, La=1-2nm (average width of carbon grains), Lc=0.5-1nm (average thickness of carbon grains), and specific surface area=1-15m 2 / g.
[0031] Among them, the high-quality hard carbon obtained by the present invention has a smaller grain size and a larger interlayer spacing, which can provide more ion diffusion channels, thereby increasing the transmission rate of sodium ions and improving the charge and discharge rate.
[0032] The present invention also provides hard carbon, which is obtained by the hard carbon purification method.
[0033] The present invention also provides an application of hard carbon obtained by the hard carbon purification method in preparing negative electrode materials for sodium ion batteries.
[0034] The technical solution of the present invention achieves the following beneficial technical effects:
[0035] (1) The present invention utilizes air flow mill ultrafine grinding combined with buoyancy separation to remove some inferior components and screen out hard carbon powder with better sodium storage performance. The process is simple, green and environmentally friendly, low-cost, and has good universality.
[0036] (2) The dispersion solution of the present invention uses ethanol and / or deionized water as solvent, polyvinyl pyrrolidone or polyethylene glycol as dispersant, and sodium chloride as solute. By adjusting the ratio of each component in the solution, the dispersion ability of hard carbon in the solution is improved, and it is convenient to sort and obtain hard carbon powder with excellent structural properties. The carbon interlayer spacing of the high-quality hard carbon obtained by the present invention is ≥0.38nm, La=1-2nm, Lc=0.5-1nm, and the specific surface area is 1-15m 2 / g.
[0037] (3) The purified hard carbon of the present invention significantly improves its sodium storage capacity and cycle stability, and improves the practical application value of hard carbon. Among them, the electrode material prepared by the purified hard carbon of the present invention has a first discharge specific capacity of 396.2mAh / g and a first efficiency of 88.9%; the capacity retention rate after 100 cycles can reach 98.0%. It is significantly better than the electrochemical performance of unpurified and sorted hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the SEM image of starch hard carbon before and after purification in Example 1 of the present invention;
[0039] Figure 2 This is a comparison diagram of XRD before and after purification of starch hard carbon in Example 1 of the present invention;
[0040] Figure 3 This is the XRD comparison diagram of starch hard carbon before and after purification in Example 3 of the present invention;
[0041] Figure 4 This is the XRD comparison diagram of starch hard carbon before and after purification in Example 5 of the present invention;
[0042] Figure 5 The first three charge-discharge curves of the electrode prepared from the original starch hard carbon in Examples 1-5 of the present invention;
[0043] Figure 6 This is a graph of the cycle performance of the electrode prepared from the original starch hard carbon in Examples 1-5 of the present invention.
[0044] Figure 7 The first three charge-discharge curves of the electrode prepared by high-quality starch hard carbon in Example 1 of the present invention;
[0045] Figure 8This is a cycle performance diagram of the electrode prepared from high-quality starch hard carbon in Example 1 of the present invention;
[0046] Fig. 9 The first three charge-discharge curves of the electrode prepared by high-quality starch hard carbon in Example 3 of the present invention;
[0047] Fig.10 This is a cycle performance diagram of the electrode prepared from high-quality starch hard carbon in Example 3 of the present invention;
[0048] Fig.11 The first three charge-discharge curves of the electrode prepared by high-quality starch hard carbon in Example 5 of the present invention;
[0049] Fig.12 This is a cycle performance diagram of the electrode prepared with high-quality starch hard carbon in Example 5 of the present invention. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and technical effect of the invention of this application clearer, the technical scheme in the embodiment of this application will be clearly and completely described below in conjunction with the drawings in the embodiment of this application. Obviously, the described embodiment is a part of the embodiment of this application, not all the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0051] The purification method and application of hard carbon of the present invention are described in detail below through specific examples.
[0052] The preparation method of the hard carbon used in the following examples is as follows: the hard carbon raw material (starch, asphalt or bagasse) is crushed to 100 mesh, placed in a nitrogen atmosphere furnace and calcined at 1300°C for 2h to obtain various hard carbon materials;
[0053] Example 1
[0054] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0055] (1) The starch hard carbon is subjected to ultrafine grinding by jet milling, and starch hard carbon powder with a particle size of D50 = 8 μm is selected;
[0056] (2) 5 g of starch hard carbon powder was dispersed in a solution (including 150 g of ethanol, 150 g of deionized water and 10 g of polyethylene glycol), and stirred at 500 rpm for 1 h to obtain a suspension;
[0057] Among them, some hard carbons with low density, large specific surface area and light weight have poor sodium storage performance and will be suspended in the upper layer of water, so the inferior hard carbon can be removed.
[0058] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0059] Figure 1 The SEM images of starch hard carbon before and after purification of Example 1. After sorting and purification, small particles and irregular hard carbon are removed, and the particle size of hard carbon is more uniform, which is conducive to improving the processing performance and stability of hard carbon.
[0060] Example 2
[0061] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0062] (1) The starch hard carbon is subjected to ultrafine grinding by jet milling, and starch hard carbon powder with a particle size of D50 = 8 μm is selected;
[0063] (2) dispersing 5 g of starch hard carbon powder in a solution (comprising 300 g of ethanol and 10 g of polyethylene glycol), stirring at 500 rpm for 1 h to obtain a suspension;
[0064] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0065] Example 3
[0066] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0067] (1) The starch hard carbon is subjected to ultrafine grinding by jet milling, and starch hard carbon powder with a particle size of D50 = 8 μm is selected;
[0068] (2) dispersing 5 g of starch hard carbon powder in a solution (comprising 300 g of deionized water and 10 g of polyethylene glycol), stirring at 500 rpm for 1 h to obtain a suspension;
[0069] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0070] Example 4
[0071] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0072] (1) The starch hard carbon is subjected to ultrafine grinding by jet milling, and starch hard carbon powder with a particle size of D50 = 8 μm is selected;
[0073] (2) dispersing 5 g of starch hard carbon powder in a solution (comprising: 300 g of deionized water, 30 g of sodium chloride and 10 g of polyethylene glycol), stirring at a speed of 500 rpm for 1 h to obtain a suspension;
[0074] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0075] Example 5
[0076] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0077] (1) The starch hard carbon is subjected to ultrafine grinding by jet milling, and starch hard carbon powder with a particle size of D50 = 8 μm is selected;
[0078] (2) dispersing 5 g of starch hard carbon powder in a solution (comprising: 300 g of deionized water, 60 g of sodium chloride and 10 g of polyethylene glycol), stirring at a speed of 500 rpm for 1 h to obtain a suspension;
[0079] Among them, some hard carbons with low density, large specific surface area and light weight have poor sodium storage performance and will be suspended in the upper layer of water, so the inferior hard carbon can be removed.
[0080] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0081] Example 6
[0082] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0083] (1) The pitch hard carbon is subjected to ultrafine grinding by jet milling, and the pitch hard carbon powder with a particle size D50 = 6 μm is selected;
[0084] (2) 5 g of pitch hard carbon powder was dispersed in a solution (comprising 300 g of deionized water and 10 g of polyvinyl pyrrolidone), and stirred at 500 rpm for 1 h to obtain a suspension;
[0085] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0086] Example 7
[0087] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0088] (1) The bagasse hard carbon is subjected to ultrafine grinding by jet mill, and the bagasse hard carbon powder with a particle size D50 = 8 μm is selected;
[0089] (2) dispersing 5 g of bagasse hard carbon powder in a solution (comprising: 300 g of deionized water, 10 g of polyvinyl pyrrolidone and 30 g of sodium chloride), stirring at a speed of 500 rpm for 1 h to obtain a suspension;
[0090] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0091] Example 8
[0092] This embodiment provides a method for purifying hard carbon, comprising the following steps:
[0093] (1) Grinding the bagasse hard carbon by jet mill, and selecting the bagasse hard carbon powder with particle size D50=8um after air selection;
[0094] (2) dispersing 5 g of bagasse hard carbon powder in a solution (comprising: 300 g of deionized water, 10 g of polyvinyl pyrrolidone and 60 g of sodium chloride), stirring at a speed of 500 rpm for 1 h to obtain a suspension;
[0095] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0096] Comparative Example 1
[0097] This comparative example provides a method for purifying hard carbon. The difference from Example 1 is that no dispersant is used in step (2). This comparative example includes the following steps:
[0098] (1) The starch hard carbon is subjected to ultrafine grinding by jet milling, and starch hard carbon powder with a particle size of D50 = 8 μm is selected;
[0099] (2) 5 g of starch hard carbon powder was dispersed in a solution (including 150 g of ethanol and 150 g of deionized water), and stirred at 500 rpm for 1 h to obtain a suspension;
[0100] (3) The suspension is allowed to stand for 24 hours, and the upper suspended hard carbon and the lower deposited hard carbon are separated. The lower deposited hard carbon is retained, filtered and washed with deionized water for 5 times, and vacuum dried for 24 hours to obtain high-quality hard carbon.
[0101] Application Examples
[0102] ① XRD analysis was performed on the original hard carbon (material crushed by air jet mill in step (1)) used in Examples 1-8 and Comparative Example 1, and the obtained high-quality hard carbon. The interlayer spacing and grain size of the hard carbon before and after purification are shown in Table 1.
[0103] Table 1 Interlayer spacing and grain size of hard carbon before and after purification
[0104]
[0105] Wherein, (002) (°): position of hard carbon characteristic peak (002); d (nm): interlayer distance of hard carbon; La (nm): average width of hard carbon grains; Lc (nm): average height of hard carbon grains.
[0106] XRD comparison of starch hard carbon before and after purification in Example 1 of the present invention, as shown in Figure 2 The (002) peak of the purified high-quality hard carbon moves to a lower angle. The interlayer spacing calculated by the Bragg equation is 0.381 nm, which is larger than the interlayer spacing of the unpurified hard carbon (0.374 nm) (Table 1). The increase in interlayer spacing is conducive to the embedding and extraction of sodium in the hard carbon. The decrease in grain size indicates that the degree of graphitization of Example 1 is lower. Its specific surface area is 2.36 m 2 / g, which is smaller than the specific surface area of the original starch hard carbon (3.08m 2 / g, this is because after sorting, the lightweight hard carbon with large specific surface area is removed, which is beneficial to improving the sodium storage capacity and the first coulombic efficiency.
[0107] XRD comparison of starch hard carbon before and after purification in Example 3 of the present invention, as shown in Figure 3 As shown. The (002) peak of the purified high-quality hard carbon moves to a lower angle ( Figure 3 ), the interlayer spacing calculated by the Bragg equation is 0.385nm (Table 1), which is larger than that of unpurified hard carbon. The surface area of the purified high-quality hard carbon is 1.75m 2 / g is smaller than the specific surface area of the original starch hard carbon 3.08m 2 / g. This is because after sorting, the lightweight hard carbon with large specific surface area is removed, which is beneficial to improving the sodium storage capacity and the first coulombic efficiency.
[0108] XRD comparison of starch hard carbon before and after purification in Example 5 of the present invention, as shown in Figure 4 As shown in Figure 2, the interlayer spacing d did not change significantly after purification. The surface area of the purified high-quality hard carbon was 2.75 m 2 / g is smaller than the specific surface area of the original starch hard carbon 3.08m 2 / g. This is because the density of sodium chloride aqueous solution is higher than that of starch hard carbon, and a good sorting effect cannot be achieved. For starch hard carbon, since the tap density of starch hard carbon is lower, the effect of direct water is more obvious.
[0109] According to the differences in the hard carbons obtained in Examples 1-5, by adjusting the ratio of ethanol-water-sodium chloride, a solution density with gradually increasing density is obtained. After sorting, hard carbon with larger La and Lc can be obtained. In addition, the interlayer spacing of carbon is also increased after sorting, among which the interlayer spacing of Examples 1, 3, and 4 is significantly improved. The increase in interlayer spacing is conducive to the embedding and extraction of sodium ions, thereby improving the capacity of the electrode.
[0110] According to the comparison between Example 1 and Comparative Example 1, it can be seen that no dispersant is added to the solution, the carbon material is prone to agglomeration, so that the structural change of the hard carbon after sorting is not obvious, and thus a satisfactory sorting effect is not achieved.
[0111] The present invention is also applicable to other types of hard carbon materials, such as asphalt hard carbon (Example 6) and bagasse hard carbon (Examples 7-8). After sorting, La, Lc and interlayer spacing d increase, and the specific surface area decreases.
[0112] ② The original hard carbon used in Examples 1-8 and Comparative Example 1 (the material after air flow milling and air separation in step (1)) and the obtained high-quality hard carbon are used as raw materials to prepare electrode slurries. The preparation method of the electrode slurry is as follows: take 0.16g of high-quality hard carbon, 0.02g of sodium alginate, 0.02g of Super-P and 0.8g of deionized water, place them in a high-speed stirrer and disperse them evenly, adjust the slurry viscosity to an appropriate level, and vacuum seal it for use.
[0113] The preparation and testing method of the hard carbon electrode is as follows: the obtained electrode slurry is evenly coated on a copper foil, vacuum dried at 80° C. for 12 hours to obtain a negative electrode sheet, and then cut to obtain a battery negative electrode sheet.
[0114] The prepared materials were assembled in a vacuum glove box in the order of negative electrode shell-negative electrode sheet-glass fiber membrane-electrolyte-sodium sheet-gasket-spring sheet-positive electrode shell, and then put into a button cell packaging machine for sheet pressing. The electrolyte was 1M NaPF6 / diethylene glycol dimethyl ether solution. The pressed battery was left horizontally for 24 hours for testing.
[0115] Using LAND blue battery charge and discharge tester, at 50mA g -1 The charge and discharge performance test was carried out in the current density range of 0.01-2V, and the test temperature was kept constant at 25°C. The test results are shown in Table 2.
[0116] Table 2 Electrochemical properties of hard carbon before and after purification
[0117]
[0118] Figure 5The first three charge-discharge curves of the original starch hard carbon electrode in Examples 1-5 and Comparative Example 1 of the present invention. The first discharge specific capacity is 277.1 mAh g -1 , the first efficacy is 85.7% ( Figure 5 , Table 2). Figure 6 The cycling performance curves of the original starch hard carbon electrode in Examples 1-5 and Comparative Example 1 of the present invention show that the discharge capacity after 100 cycles is 269.2 mAh g -1 , the cycle retention rate is 97.1%.
[0119] Figure 7 The first three charge-discharge curves of the purified starch hard carbon electrode in Example 1 of the present invention are shown in Figure 1. The first discharge specific capacity is 396.2 mAh g -1 , the first efficacy is 83.2%. Figure 8 This is the cycle performance curve of the purified starch hard carbon electrode in Example 1 of the present invention. After 100 cycles, the discharge capacity is 336.2 mAh g -1 , the cycle retention rate is 84.9%.
[0120] Fig. 9 The first three charge-discharge curves of the purified starch hard carbon electrode in Example 3 of the present invention are shown. The first discharge specific capacity is 332.6 mAh g -1 , the first efficacy is 82.8%. Fig.10 This is the cycle performance curve of the purified starch hard carbon electrode in Example 3 of the present invention. After 100 cycles, the discharge capacity is 326.1 mAh g -1 , the cycle retention rate is 98%.
[0121] Fig.11 The first three charge-discharge curves of the purified starch hard carbon electrode in Example 5 of the present invention are shown. The first discharge specific capacity is 304.4 mAh g -1 , the first efficacy is 86.8%. Fig.12 This is the cycle performance curve of the purified starch hard carbon electrode in Example 5 of the present invention. After 100 cycles, the discharge capacity is 281.3 mAh g -1 , the cycle retention rate is 92.4%.
[0122] From Table 2, based on the comparison of Examples 1-5, it can be seen that with the different ratios of the sorting solutions, the degree of performance improvement of the obtained high-quality hard carbon electrode materials is also different, which is mainly reflected in the discharge specific capacity and the first coulombic efficiency. This is attributed to the increase in the carbon layer spacing and the increase in the grain size. Among them, Example 1 shows the highest discharge specific capacity, and Example 2 shows the highest first coulombic efficiency.
[0123] According to the comparison between Example 1 and Comparative Example 1, the separation and purification effect is not obvious due to the absence of dispersant. The discharge capacity of the hard carbon electrode in Comparative Example 1 is slightly improved, but the first coulomb efficiency and cycle retention rate are reduced (Table 2).
[0124] In addition, for pitch hard carbon (Example 6) and bagasse hard carbon (Examples 7 and 8), the sodium storage performance of the hard carbon electrode is also significantly improved after sorting and purification. Comparing Example 7 and Example 8, it can be seen that compared with the relatively single cost of starch raw materials, since bagasse contains multiple tissues such as sugarcane skin and sugarcane pith, the density of bagasse hard carbon is larger, the component structure is more complex, and the proportion of inferior hard carbon is also higher. A higher density sorting solution is required to obtain a better bagasse hard carbon material.
[0125] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for purifying high-quality hard carbon, characterized in that: The following steps are involved: (1) ultrafinely grinding hard carbon to obtain hard carbon powder; (2) dispersing hard carbon powder in a solution and stirring to obtain a suspension; (3) Allow the suspension to stand, separate and retain the lower layer, wash and dry to obtain the product.
2. The purification method according to claim 1, characterized in that In step (1), the hard carbon is obtained by carbonizing a hard carbon raw material at high temperature under an inert atmosphere; The hard carbon raw material is a mixture of any one or more of starch, asphalt, bagasse, eucalyptus, glucose, straw, reed, peanut shell, palm shell or macadamia shell; The specific method of high temperature carbonization is: crush the hard carbon raw material into 100 meshes, place it in a nitrogen atmosphere furnace and calcine it at 1300° C. for 2 hours.
3. The purification method according to claim 1, characterized in that In step (1), the particle size of the hard carbon powder is D50=3-50 um; In step (2), the solution comprises the following components, by weight: 200-400 parts of solvent, 0-80 parts of solute and 10-20 parts of additive.
4. The purification method according to claim 3, characterized in that In step (2), the solvent is ethanol and / or deionized water; the solute is sodium chloride; and the additive is polyvinyl pyrrolidone or polyethylene glycol; When the solvent is ethanol and deionized water, the mass ratio of ethanol to deionized water is 1:
1.
5. The purification method according to claim 4, characterized in that In step (1), when the hard carbon is starch, asphalt, glucose, straw, reed or peanut shell, in step (2), the solution comprises the following components by weight: 300 parts of solvent and 10 parts of additive; Or, in step (1), when the hard carbon is bagasse, eucalyptus, palm shell or macadamia shell, in step (2), the solution comprises the following components by weight: 300 parts of solvent, 30-60 parts of solute and 10 parts of additive.
6. The purification method according to claim 1, characterized in that In step (2), the mass ratio of the hard carbon powder to the solvent in the solution is 1:(50-70); In step (2), the stirring speed is 400-600 rpm and the stirring time is 1-2 h.
7. The purification method according to claim 1, characterized in that In step (3), the standing time is 22-26 hours; the drying time is 22-26 hours; the specific separation method is: separating the upper suspended hard carbon and the lower deposited hard carbon, and retaining the lower deposited hard carbon.
8. The purification method according to claim 1, characterized in that In step (3), the obtained high-quality hard carbon has a carbon interlayer spacing of ≥0.38nm, La = 1-2nm, Lc = 0.5-1nm, and a specific surface area of 1-15m 2 / g.
9. A high-quality hard carbon, characterized in that: The high-quality hard carbon is obtained by the purification method of high-quality hard carbon according to any one of claims 1 to 8.
10. Use of the high-quality hard carbon as claimed in claim 9 in preparing negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Biomass-based sodium ion battery hard carbon negative electrode material
CN108439363A
Modified hard carbon for electrode slurry as well as preparation method and application of modified hard carbon
CN118479453A
